Cellular mechanisms of taste disturbance induced by the non-steroidal anti-inflammatory drug, diclofenac, in mice - Hirayama, Ayaka; Iwata, Shusuke; Oike, Asami; Kawabata, Yuko; Nagasato, Yuki; Takai, Shingo; Sanematsu, Keisuke; Takahashi, Ichiro; Shigemura, Noriatsu (Frontiers in Cellular Neuroscience, 2023)
Drug-induced taste disorders are a serious problem in an aging society. This study investigated the mechanisms underlying taste disturbances induced by diclofenac, a non-steroidal anti-inflammatory drug that reduces pain and inflammation by inhibiting the synthesis of prostaglandins by cyclooxygenase enzymes (COX-1 and COX-2). RT-PCR analyses demonstrated the expression of genes encoding arachidonic acid pathway components such as COX-1, COX-2 and prostaglandin synthases in a subset of mouse taste bud cells. Double-staining immunohistochemistry revealed that COX-1 and cytosolic prostaglandin E synthase (cPGES) were co-expressed with taste receptor type-1 member-3 (T1R3), a sweet/umami receptor component, or gustducin, a sweet/bitter/umami-related G protein, in a subset of taste bud cells. Long-term administration of diclofenac reduced the expression of genes encoding COX-1, gustducin and cPGES in mouse taste buds and suppressed both the behavioral and taste nerve responses to sweet and umami taste stimuli but not to other tastants. Furthermore, diclofenac also suppressed the responses of both mouse and human sweet taste receptors (T1R2/T1R3, expressed in HEK293 cells) to sweet taste stimuli. These results suggest that diclofenac may suppress the activation of sweet and umami taste cells acutely via a direct action on T1R2/T1R3 and chronically via inhibition of the COX/prostaglandin synthase pathway inducing down-regulated expression of sweet/umami responsive components. This dual inhibition mechanism may underlie diclofenac-induced taste alterations in humans.